Rootstock developments in avocado: Selection of rootstocks for biotic and abiotic stress mitigation - Gayathri, S; Shanmugasundaram, K A; Auxcilia, J; Shanthi, A; Karthikeyan, M; Muthuvel, I (Plant Science Today, 2025)
Avocado (Persea americana Mill.) is a globally important fruit crop that is vulnerable to various biotic and abiotic stresses prevalent in subtropical regions, significantly affecting productivity. Rootstocks play a crucial role in mitigating stress factors and ensuring sustainable avocado cultivation. This review discusses the propagation methods for avocado rootstocks, including seed and clonal propagation techniques and examines the responses of different rootstocks to abiotic stresses such as salinity, poorly aerated soils, calcareous, alkaline soils and drought. It highlights the physiological, biochemical and molecular mechanisms involved in these stress responses. This review also covers resistance of various rootstocks against biotic stresses, including Laurel wilt (Harringtonia lauricola), root rot (Phytophthora cinnamomi), white root rot (Rosellina necatrix) and Verticillium wilt (Verticillium dahliae). Extensive research has identified promising rootstocks such as R0.05, Dusa, PP40 and R0.18 for salinity tolerance; West Indian rootstocks for tolerance to calcareous soils and rootstocks such as Duke 7, Toro Canyon and BG-83 for resistance against various other diseases. Understanding defense mechanisms such as callose deposition, lignification and pathogenesis-related protein production, will aid in developing molecular markers and screening techniques for tolerant rootstock selection. These specialized avocado rootstocks offer specific tolerance, making them ideal for diverse growing conditions. Enhancing stress resistance leads to more productive trees, which significantly boost the sustainability and profitability of commercial avocado cultivation.